2020
DOI: 10.1002/adom.202001763
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable CsPbX3/PbSO4 Core/Shell Nanocrystals Synthesized by a Simple Post‐Treatment Strategy

Abstract: All‐inorganic lead halide perovskite (CsPbX3, X = Cl, Br, I, or their mixture) nanocrystals (NCs) have recently emerged as a promising photoelectric material; however, developing highly stable CsPbX3 NCs still remains a challenge due to their intrinsic ionic nature. This work presents a simple and facile post‐treatment strategy to encapsulate CsPbX3 NC with PbSO4 nanoshell at single‐particle level. Compared to pristine CsPbX3 NCs, the as‐prepared CsPbX3/PbSO4 NCs exhibit significant enhancement in the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…The results described here are apparently similar to those obtained by the post-treatment of Octam-SO 4 , except that our treatment time is much longer. In fact, by choosing a different source of SO 4 2– , and on purposely lowering the dosage, we managed to slow down the reaction rate, which brings at least two benefits.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The results described here are apparently similar to those obtained by the post-treatment of Octam-SO 4 , except that our treatment time is much longer. In fact, by choosing a different source of SO 4 2– , and on purposely lowering the dosage, we managed to slow down the reaction rate, which brings at least two benefits.…”
supporting
confidence: 89%
“…Cao et al reported a quick post-treatment using octylammonium sulfate (Octam-SO 4 ) which helps to enhance the PLQE and the stability of CsPbX 3 (X = Cl, Br) QDs. 31 Later, we proposed a surface sacrificial reaction using octylammonium phosphate, which delivered CsPbBr 90% and superior overall stability. 32 We found that, on one hand, the bonding between oxysalt ions and the lowcoordinated Pb not only passivates surface defects but also provides a protecting shell on the surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies have been designed to prevent anion exchange and/or to stabilize MHP NCs against polar solvents, including encapsulation of NCs in matrixes made of metal oxides (e.g., PbSO 4 , SiO 2 , TiO 2 , Al 2 O 3 ), inorganic salts (SrBr 2 ), a mixture of metal oxides and inorganic salts, metal organic hybrids (e.g., metal organic frameworks), and polymers. ,, Polymers are appealing as they can switch their chains from an extended coil state to a collapsed globule state when the characteristics of the solvent change. In its globule state, a polymer can act as a protecting layer that shields the NCs from their surroundings, making them unreactive.…”
mentioning
confidence: 99%
“…For example, Zhang and coworkers reported a simple post-treatment strategy to encapsulate CsPbX 3 NCs with PbSO 4 nanoshell through mixing octylammonium sulfate (OctAm-SO 4 ) with CsPbX 3 NCs, demonstrating great stability against polar solvents and irradiation. [16] However, there was a lack of LED devices in this report, which may be ascribed to the poor dispersion of the as-treated CsPbX 3 NCs that cannot be applied in the emissive layers of LEDs.…”
Section: Introductionmentioning
confidence: 69%